2016
DOI: 10.1007/s13277-016-4902-8
|View full text |Cite
|
Sign up to set email alerts
|

A truncated phosphorylated p130Cas substrate domain is sufficient to drive breast cancer growth and metastasis formation in vivo

Abstract: Elevated p130Cas (Crk-associated substrate) levels are found in aggressive breast tumors and are associated with poor prognosis and resistance to standard therapeutics in patients. p130Cas signals majorly through its phosphorylated substrate domain (SD) that contains 15 tyrosine motifs (YxxP) which recruit effector molecules. Tyrosine phosphorylation of p130Cas is important for mediating migration, invasion, tumor promotion, and metastasis. We previously developed a Src*/SD fusion molecule approach, where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…4A). Our previous studies and others indicated that p130Cas is a proto-oncogene governing cell migration/invasion and its differential expression is related to cancer progression15162027. To test whether miR-24-3p regulates p130Cas expression, we investigated p130Cas expression in MCF7 cells after the transfection of miR-24-3p.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). Our previous studies and others indicated that p130Cas is a proto-oncogene governing cell migration/invasion and its differential expression is related to cancer progression15162027. To test whether miR-24-3p regulates p130Cas expression, we investigated p130Cas expression in MCF7 cells after the transfection of miR-24-3p.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that p130Cas promotes the growth and migration of cancer cells and its expression was found to be augmented in several cancers14151617. Since p130Cas has the potential as a proto-oncogene, the mechanisms regulating p130Cas expression and activity needs to be understood.…”
mentioning
confidence: 99%
“…For example, overexpression of Cas in MMTVHER2Neu transgenic mice accelerates the timeto tumorappearance while Cas depletion in a TGFβ driven model of mammary tumorigenesis significantly reduces tumor outgrowth (Cabodi et al, 2006, Wendt, Smith, & Schiemann, 2009. Furthermore, overexpression of the phosphorylated substrate domain of Cas in MMTVpolyoma middle T (PyMT) mice accelerates tumor growth and promote metastasis (Zhao et al, 2013;Kumbrink et al, 2016). Src activity enhances cell growth, proliferation, angiogenesis, invasion, and metastasis (Finn, 2008).…”
Section: Bcar3 Targeting To Adhesions Is Multi-factorialmentioning
confidence: 99%